Community-based oral cancer screening for women of remote & rural blocks of the Chikkaballapur district, Karnataka, India - Kunal Oswal; Mayank Chhabra; Bharat Kumar Sarvepalli; Sripriya Rao; Moni Abraham Kuriakose; Venkataramanan R (Elsevier, 2023)
Background: Oral cancer accounts for approximately one-third of all cancers in India with the majority of these cases estimated to be advanced at presentation, due to a higher proportion of the population consuming tobacco or related products. This could be attributed to habits and cultural factors, leading to a higher prevalence of tobacco-related lesions of the oral cavity. Both early screening and surveillance can enable in early detection of oral cancer in such high-risk populations. Objective: The study aims to estimate the prevalence of Oral Potential Malignant disease (OPMD) among the population and link it with the lifestyles and risk factors for oral cancer. A better understanding of their pattern and behavior practice within the community is a must. Methodology: Cross-sectional study was performed on 4974 rural women in the 35-60 years age group through community screening camps organized from September 2021 to November 2021 around Chikkaballapur districts of Karnataka, India. Data was recorded through a digital application and with informed user consent. Results: We attempt to identify the important risk factors associated with an increased risk including habits such as tobacco, smoking and related products. The prevalence of OPMD varied for all talukas, Mandikal (13.45), Nandi (9.68) and Bagepally (5.09). The most commonly encountered OPMD was leukoplakia (59.2) followed by erythroplakia (31.4), oral submucous fibrosis (6.8) and lichen planus (2.6) were also seen. Conclusion: This study provides strong evidence that tobacco and related products could be a straight line responsible for developing OPMD.